(untitled) (Research, Society and Development, 2020)
This study aims to understand and identify how the decision process by a publisher for the publication of scientific, technical and professional books (CTPs) adopted by UFSM professors. Due to the particularities, this research was based on Zeithaml and Bitner and Blackwell et al., as well as papers focusing on the decision-making process of Prado and Barcellos. This work can be classified as a descriptive exploratory research, with a qualitative approach, carried out through semistructured interviews and examined through the content analysis technique. The subjects of the research were formed by the professors linked to the Federal University of Santa Maria, who have published at least one book as author or organizer of the work. Among the results obtained, it begins with the characterization of the 20 participating authors’ personal and professional profiles, besides its publications; followed by the identification and systematization of the decision process adopted by UFSM teachers in choosing a publisher, through the search for information, evaluation of alternatives, consumption of services and post-consumer evaluation. Also, the decision strategies used by the participants to choose a publisher company were identified, evidencing, among other aspects, the low loyalty factor for decision in book publishing and that the choice based mainly on attributes, having a dependency relation of with the intention of the author with its book. Finally, improvements are proposed in the management practices of UFSM’s Publishing Company (Editora UFSM) that acts in accordance with the demands of the authors, verified from the identified criteria.